LITERATURE IN INCREASING ECOLOGICAL AWARENESS IN THE ERA OF INDUSTRIAL REVOLUTION 5.0. - Nahdhiyah Nahdhiyah; Sardian Maharani (Elite : English and Literature Journal, 2023)
The Industrial Revolution 5.0 is an integration of advanced technology and human expertise. The era that focuses on improving the quality of life and human welfare by optimizing the use of limited natural resources but still environmentally friendly forces people to be adaptive to the orientation of that era. Based on the core of literature as dulce et utile, beautiful and meaningful or useful (Horatius), this study intends to find and show the meaningfulness and contribution of literary work as a medium in increasing ecological awareness in era of Industrial Revolution 5.0. As a perspective to understand environmental problems, ecological literature (Eco Literature) was chosen as an approach to find answers in this research. The research method is hermeneutic method. The object of research is novel. The selected novels are Dunia Anna and The Overstory. The characters in the two novels are described as having ecological awareness. They are aware about the importance of preserving the environment so that the earth is not damaged but could benefit to future generations. The characters are described as carrying out a mission to save the environment and making efforts to restore the state of the environment. This is in line with the vision of Industrial Revolution 5.0 which prioritizes environmentally friendly concepts. Ecological awareness messages in these two novels provide evidence that novels as literary works contain life learning values ​​that are useful, contributive and deserve to be taught and disseminated.